Developing a Neuronal Differentiation Score for quantitative assessment of glutamatergic differentiation in human neuroblastoma cells - Lina Lin; Wenlong Yan; Enze Zhang; Wenjie Xu; Xiaokai Sui; Hui Zheng; Ting Xiao; Cheng Ni (Tissue and Cell, 2027)

Proteomic and metabolomic analysis of Litopenaeus vannamei infected with infectious hypodermal and hematopoietic necrosis virus (IHHNV) - Fan Yang; Shou-Xin Luo; Zhi-Peng Yin; Ling-Jun Si; Ting Li; Lin-Rui Chang; Dong-Chun Yan (Aquaculture, 2027)

MiR-4327 targets TP53 to promote cervical cancer cell proliferation - Mei-Lin Chen; Chen-Yang Chu; Feng-Xian Zhang; Li-Pei Zhang; Ying Yang; Bai-Zhao Peng; Chuang-Hai Wu; Xiao-Mei Chen; Yan-Ting You; Bing-Ying Rong; Hiu Yee Kwan; Xiao-Shan Zhao; et al. (Functional & Integrative Genomics, 2026)
Cervical cancer is a leading cause of female malignancy worldwide. While microRNA-4327 (miR-4327) has been implicated as a potential oncogene, its functional role and molecular mechanisms in cervical cancer pathogenesis remain unclear. This study aimed to determine the oncogenic function of miR-4327 and elucidate its downstream regulatory mechanism in cervical cancer pathogenesis. We measured miR-4327 expression in clinical cervical cancer tissues and cell lines using quantitative real-time PCR (qRT-PCR). We then assessed its effects on proliferation, migration, invasion, and cell cycle progression through functional assays including cell counting kit-8 (CCK-8), colony formation, transwell, and flow cytometry. To evaluate tumor growth in vivo, we established a xenograft model in non-obese diabetic (NOD)-severe combined immune-deficient (scid) mice. Using bioinformatic analysis and luciferase reporter assays, we identified TP53 as a direct target of miR-4327 and further validated this regulatory relationship with gain- and loss-of-function experiments. We found that miR-4327 was significantly upregulated in cervical cancer and promoted malignant phenotypes such as proliferation, migration, invasion, and cell cycle progression in vitro. Consistent with this, overexpression of miR-4327 accelerated tumor growth in vivo. Mechanistically, we confirmed TP53 as a direct functional target of miR-4327. Knocking down TP53 phenocopied the oncogenic effects of miR-4327, while restoring TP53 expression rescued the tumor-promoting effects mediated by miR-4327. These findings reveal a novel miR-4327/TP53 regulatory axis and nominate miR-4327 as a potential therapeutic target for intervention.

Bushen Yijing formula exerts chondroprotective effects in knee osteoarthritis via the ERα/PI3K/AKT signaling pathway: Insights from network pharmacology and experimental validation - Yu-Qing Zhai; Jian-Wei Lu; Qiang Yan; Jia-Wei Du; Yang-Shuo Ge; Min-Jun Zhao; Jian-Li Yin; Chun-Meng Huang; Ting-Ting Meng; Xin-Hui Huang; Liao-Lin Chen; Jia-Hui Luo; et al. (Tissue and Cell, 2026)

Mesozoic crustal thinning in the northern North China Craton: Evidence from Triassic and Jurassic plutons in the Huyu area, northwestern Beijing - Liang Qiu; Dan-Ping Yan; Jun-Ting Qiu; Wei Yang; Yiyu Lin; Suhua Cheng; Xiuhua Cao; Xuchao Chai; Pei Zhang; Lei Gao; Zeyilin Ma (Journal of Asian Earth Sciences, 2026)

Recoverable millimeter-sized poly(ether-ether-ketone)-based adsorbent beads with multisite complexation for Co2+/Ni2+ removal from radioactive wastewater - Peng-De Yu; Yan-Lin Ren; Wen-Juan Wang; Ya-Juan Cai; Ting Yue; Ke-Xiao Sang; Yi-Xing Sun; Dan Wu; Zi-Hao Yang; Chuan-Zhe Zhao; Ying-Kang Li; Ya-Ge Wu; et al. (Journal of Environmental Chemical Engineering, 2026)

Differential effects of alcohol-derived serum metabolites and direct ethanol exposure on mouse preantral follicle development - Meng-Ting Cao; Yang Shi; Chun Li; Yi-Lin Fan; Zhu-Rong Hu; Le-Ning Dang; Xue-Rui He; Wei-Qiang Luo; Jing-Jing Li; Xing-Rong Yan (Chemico-Biological Interactions, 2026)

Postbiotics mitigate translucent post-larvae disease (TPD) in Penaeus vannamei by reinforcing hepatopancreatic cytoskeletal integrity against VHVP-2 toxin - Wenqiang Li; Shuang Liu; Jin Yan; Ping Li; Tingting Xu; Jin-Seng Lin; Hsiao-Tung Chang; Ting-Yu Lee; Qingli Zhang (Aquaculture, 2026)

PFAS associated with dysglycemia and glucose trajectories: a prospective cohort study from the Isomers of C8 Health Project in China - Wen-Qi Yang; Yun-Ting Zhang; Wen-Yu Wang; Haseeb Tufail Moryani; Muhammad Amjad; Zeeshan Mohammed; Xuan Liu; Yan-Xu Chen; Kun Zhao; Chu Chu; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Co-exposure to PFAS, PFAS alternatives, and metals and liver function in Chinese adults - Shui-Yue Lu; Jing-Lin Zhang; Nuo Chen; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Xuan Liu; Yan-Xu Chen; Jia-Xin Zhou; Wen-Wen Bao; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

A chitosan-based cinnamaldehyde–raspberry ketone integrated carrier architecture for oral delivery toward mild metabolic regulation - Yu-Chi Wang; Sin-Huei Chuang; Chien-Fu Lin; Yan-Ting Lin; You-Song Cheng; Chih-Chen Lin; Chi-Chen Ting; Wei-Han Chen; Ting-Yu Chen; Shen-Ho Kuo; Fu-I Tung; Tse-Ying Liu (Carbohydrate Polymers, 2026)

Decoupling of mass-based and oxidative-potential-based source contributions to PM2.5 in Nanjing: Random forest combined with PMF analysis - Yan-Yu Chen; Fang Cao; Chang-Liu Wu; Xiao-Ying Yang; Yu-Ting Mei; Yuan Dai; Meng-Ying Bao; Wen-Huai Song; Yan-Lin Zhang (Atmospheric Environment, 2026)

Correction: The dynamic evolution of circulating tumor cells during glecirasib treatment predicts survival and resistance in gastrointestinal tumors with KRASG12C mutation - Lei Jiang; Yiming Luo; Huan Liang; Xujiao Feng; Yan Huang; Yanyan Li; Zhenghang Wang; Ting Xu; Heng Zou; Zhi Li; Lin Shen; Yang Chen; et al. (Human Cell, 2026)

Wettability-switchable deep bed filtration for efficient oily wastewater treatment - Song Xichen; Yan Yaping; Zhang Tingting; Zhou Jianqiang; Wang Xiaojuan; Wang Zhezhe; Lin Jialong; Wang Ting; Song Xiaosan; Dai Liang; Wang Gang; Gao Suxia; et al. (Journal of Hazardous Materials, 2026)

Unveiling precursor-derived PFAS burdens in landfill leachate: TOP assay reveals ultrashort-chain PFAS and DTRO removal limitations across 11 Chinese cities - Ying Zhang; Nemin Luo; Bin Yan; Lei Wang; Haolong Zhang; Mingyuan Lin; Ting Fang; Zhenchang Zhong; Huiyan Cheng; Yan Lin (Journal of Environmental Sciences, 2026)

ERBB2 as a Prognostic Biomarker in Prostate Cancer: Integration of Single-Cell Transcriptomics, Deep Learning, and Immunohistochemical Validation - Chen Wang; Li-Jing Zhu; Wei-Bo Mao; Ting Chen; Teng-Fei Gu; Sheng-Ping Hu; Yong-Tao Pan; Guo-Lin Yan; Yun-Peng Dong; Jie Li (Biochemical Genetics, 2026)

Three new diterpenoids from the aerial parts of Callicarpa macrophylla - Liang Gou; Rong-Shuai Li; Jian-Lin Lai; Yan-Mei Ning; Xue-Ting Ji; Xiong Qiu; Chao Peng; Xiao-Li Li; Xing-Jie Zhang; Wei-Lie Xiao (Natural Product Research, 2026)

Role of NADPH oxidase generated O2− in seed germination and cold stress response of Brassica napus - Wei-liang Qi; Guo-yan Bao; Mei-ying Sun; Wen-juan Ma; Xuan-ting Yang; Xiang-hong Gao; Miao-xin Zhou; Qi-lin Wang (Protoplasma, 2026)

Hepatic Sirt2-PARP1-HMGB1 axis promotes exercise-mediated amelioration of MASH in mice - Shan Li; Wang-Jing Mu; Zi-Ang Zhao; Wan-Qiu Peng; Jie-Ying Zhu; Ruo-Ying Li; Lin-Jing Yan; Yang Li; Hong-Yang Luo; Min Chen; Meng-Ting Yin; Xin Li; et al. (Science China Life Sciences, 2026)

The dynamic evolution of circulating tumor cells during glecirasib treatment predicts survival and resistance in gastrointestinal tumors with KRASG12C mutation - Lei Jiang; Yiming Luo; Huan Liang; Xujiao Feng; Yan Huang; Yanyan Li; Zhenghang Wang; Ting Xu; Heng Zou; Zhi Li; Lin Shen; Yang Chen; et al. (Human Cell, 2026)

Phage-Display Identification of Urate-Binding Cyclic Peptides with Preliminary Urate-Lowering Activity in Adenine-Induced Hyperuricemic Rats - Mi Ai; Zhi-Ming Wang; Wei-Lin Guo; Xue-Qi Li; Li-Ting Xiao; Yan-Shan Mai; Hong-Bin Zhang (International Journal of Peptide Research and Therapeutics, 2026)

Mangrove species act as potential biofilters for legacy organochlorine pesticides: evidence from tissue-specific accumulation in the Zhangjiang Estuary - Nemin Luo; Ting Fang; Yingying Qian; Lei Wang; Wenhui Lin; Rongrong Song; Guoxin Li; Fengrun Wu; Xiaoqing Chen; Mingyuan Lin; Yan Lin (Marine Environmental Research, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Synthesis of ZIF-8 derived porous carbon via morphology-controlled electrodeposited ZnO thin films for in-plane micro-supercapacitors - Jun-Yan Lin; Ramasamy Velmurugan; Jing-Jie Lin; Zhi-Ting Huang; Man-Ning Lu; Martin Hulman; Chien-Kuo Hsieh; Jeng-Yu Lin (Chemical Engineering Journal, 2026)

Quantitative study on the cave environmental factors for the fractionation of stable oxygen isotopes during the deposition of speleothem - Yue Jin; Chun-Jie Wang; Jian Zhang; Wen-Jun Sun; Chao-Jun Chen; Yao Wu; Hua-Yan Li; Yue-Hua Xiang; Yue-Yuan Lin; Xin-Rui Ye; Xin-Yan Li; Zhong-Lin Deng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Chronology and geochemistry of radiolarian chert from Zhongba, southern Xizang (Tibet): Implications for the evolution of the Neo-Tethys Ocean - Han Yan; Han-Ting Zhong; Zong-Qi Lin; Chen-Yu Wang; Ling-Xue Gao; Cai Wang; Ming-Cai Hou (Palaeoworld, 2026)

Sibakazin: a novel black fly derived non-classical kazal protease inhibitor, targeting antiplatelet (P2Y12/GPVI) pathways without perturbing coagulation - Zhuorui Li; Yanmei He; Yan Shen; Miao He; Ting Lin; Jiayi Yang; Lixian Mu; Jing Wu; Hailong Yang (Insect Biochemistry and Molecular Biology, 2026)

Sn2+ doping-induced activation of inert adsorption sites in Li/Al-LDHs for selective lithium extraction from brines - Rui Zhang; Chenlu Yan; Jun Chen; Ting Wei; Jianguo Yu; Sen Lin (Chemical Engineering Journal, 2026)

Chlorine-resistant high-entropy spinel oxide catalyst for efficient and durable seawater anion exchange membrane water electrolysis - Thi Xuyen Nguyen; Ting-You Shih; Ngoc Thanh Thuy Tran; Thanh Tuan Nguyen; Yi-Chuan Chu; Bo-Han Lai; Chun-Kuo Peng; Yu-Ru Lin; Yan-Gu Lin; Kao-Shu Chuang; Jeng-Kuei Chang; Thi Y Phung Nguyen; et al. (Chemical Engineering Journal, 2026)

The occupations of microblade technology populations at Jiangjunbu02 site on the northeastern Tibetan Plateau and their relationships with paleoenvironment changes - Yuanxin Li; Juanting Yao; Xuke Shen; Linxueyi Wang; Yan Zhou; Huan Xia; Dongpeng Lin; Lin Chen; Yongxiu Lu; Jian Wang; Ting Cheng; Yan Zhao; et al. (Science China Earth Sciences, 2026)

Coupled Effects of Reservoir Level Fluctuations and Rainfall on Landslide Deformation Using InSAR and DEM Analysis - Liu Tie-biao; Liu Ming-quan; Luo Shi-lin; He Kun-lin; Yan Guang-zhi; Chen Guo-feng; Cao Su-ting (Geotechnical and Geological Engineering, 2026)

Co-exposure to Cadmium and Polystyrene Nanoplastics Intensifies Renal Damage in Mice via the Activation of the PANoptosis Pathway - Rongmei Wang; Hao Xi; Ting Ma; Jingbo Lin; Huifeng Shi; Yanming Cai; Cuiyan Zhao; Wenlong Yan (Biological Trace Element Research, 2026)

Tilapia skin collagen peptides‑calcium chelates:Structural characterization, stability, in vitro and in vivo anti-osteoporosis mechanism - Xing Xie; Meng-ting Zhang; Chun-lin Huang; Jin-yu Wang; Qiao Ding; Yan-xia Xiong; Zong-cai Tu; Lu Zhang (Food Research International, 2026)

Unraveling the aromatic essence of baked green tea using sensomics: insights from three representative cultivars - Yan Zhao; Chen-Yang Shao; Han Yan; Yue Zhang; Qun-Hua Peng; Zhi Lin; Xiao-Ting Zhai; Hai-Peng Lv; Yin Zhu (Food Chemistry, 2026)

Genetically Modified Primate Models for Brain Disorder Research - Yi Yang; Jianbang Lin; Mengqi Li; Lixin Yang; Zhonghua Lu; Ting Yan (Neuroscience Bulletin, 2026)

Research on real-time detection method of fish parasites based on the improved YOLO11n - Zhikang Lin; Xin Zhang; Yan Zhang; Juan Zou; Ting Wu; Ling Yang (Aquaculture, 2026)

Climate change and transformations of ancient civilization in the Chengdu Plain, Southwest China, during the mid-to-late Holocene - Zhong-Lin Deng; Xin-Yan Li; Ting-Yong Li (Quaternary Science Reviews, 2026)

Synergistic pathogenic mechanisms of EHP and IHHNV co-infection in Litopenaeus vannamei: Insights from RNA-seq analysis - Lin-Rui Chang; Cai-Yi Chen; Fan Yang; Chuan-Yu He; Fan Li; Ting Li; Ling-Jun Si; Dong-Chun Yan (Journal of Invertebrate Pathology, 2026)

Exploring different modification methods of biochar for Se(IV) removal from water: Synergistic effect of adsorption and reduction - Yu-Ying Wang; Juan Yu; Rong-Ting Jiao; Li-Li He; Yao Su; Yun-Long Wang; Hui Lin; Yan Shi; Hao-Hao Lyu (Journal of Contaminant Hydrology, 2026)

Sublethal exposure to an amitraz-fluvalinate-coumaphos mixture disrupts honeybee gut microbiota and sensitizes to neonicotinoid toxicity - Kang Wang; Jinmeng Ma; Ming Zheng; Yuanchan Fan; Yi Zhang; Wenan Zhang; Yan Zhang; Zheguang Lin; Ting Ji (Environmental Research, 2026)

Two birds with one stone: Constructing confined N-doped carbon catalysts to boost solar-driven interfacial water evaporation and peroxymonosulfate mediating antibiotic wastewater purification - Qi-E Zhang; Lin-Bo Deng; Hui-Qing Lv; Guo-Qing Zhao; Yan Pan; Jin Zou; Meng-Ting He; Xun-Kuan Ye; Jin-Gang Yu; Limin Lu (Environmental Research, 2026)

Structural characteristics and bioactivities of an exopolysaccharide from mycelial fermentation of a medicinal fungus Cs-HK1 - Fang Ting Gu; Jun Hui Li; Zi Chen Zhao; Yan Yu Zhu; Lin Xi Huang; Jian Yong Wu (Carbohydrate Polymers, 2026)

Icariside II sensitizes osteosarcoma to doxorubicin through the lincROR/Wnt/β-catenin signaling regulatory axis - Shu-ting Zhou; Zhi-peng Li; Yong-xin Mai; Yu-Yan Wang; Feng-xiang Pang; Jin-fang Zhang; Xian-lin Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Discovery of FLF-15 as a novel selective inhibitor of ADAM17 to prevent hepatocellular carcinoma metastasis - Qing Li; Dao-ping Wang; Ting Zhong; Ai-ling Ling-hu; Jia-lin Chen; Fang Luo; Feng Zhang; Ming-zhi Su; Ying Yang; Yan-hua Fan (Molecular Diversity, 2026)

Key factors affecting heavy metal contamination of mangrove sediments in the Zhangjiang Estuary: Implications for environmental management - Zheng Zhang; Lianzhi Zhong; Cheng Luo; Ting Fang; Lei Wang; Bin Yan; Jinpeng Wang; Xiuwen Ren; Yan Lin (Marine Pollution Bulletin, 2026)

From genes to products: High-efficiency biosynthesis and holistic optimization strategies for monounsaturated fatty acids - Lu-Wei Xu; Yan-Cheng Lin; Yi-Ting Shen; Xin Qi; Zi-Xu Zhang; Wang Ma; Xiao-Man Sun (Food Microbiology, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Disentangling seasonal dynamics and transboundary transport of PAHs in a coastal monsoon city - Haolong Zhang; Zheng Zhang; Wenhui Lin; Guohui Lin; Cheng Luo; Ting Fang; Nemin Luo; Minggang Cai; Lei Wang; Bin Yan; Yan Lin (Atmospheric Research, 2026)

Anti-diabetic quinolone alkaloids from the fruits of Tetradium ruticarpum - Chun-Lin Zhao; Kai-Wen Kang; Zhi-Cheng Su; Hong-Yan Mu; Hui-Shan Guo; Hui-Zhen Chen; Ya-Ting Chen; Jing-Wei Jin; Ju-Cai Xu; Hong-Guang Li; Li-She Gan (Phytochemistry Letters, 2025)

Tartary buckwheat-soy protein isolate composite gels: gelling, rheological, water-retention, and texture characteristics at different ratios - Xiao Han; Gen Ma; Lin Wang; Ting Cheng; Yangyang Guo; Liangzhen Jiang; Yan Wan; Xiaoqin Zheng; Changying Liu; Lianxin Peng; Gang Zhao; Xiulan Guo; et al. (Food Hydrocolloids, 2025)

Gut Microbiota Improve the Prediction of Stroke-Associated Pneumonia Risk and Outcomes in Acute Ischemic Stroke - Yi-si Lin; Jia-hao Chen; Wei-hao Zhuang; Jia-ni Huang; Yi-han Chen; Jie Zhang; Jia Li; Meng Huang; Jia-long Hou; Shuang-jie Qian; Zhi-bo Chen; Yan-lei Zhang; et al. (Translational Stroke Research, 2025)

Potent phenolics with antimigratory and anti-MRSA powers from fungus associated with Saussurea involucrata - Wei-hua Yuan; Meng-ting Teng; Lin Ma; Yan-feng Wan; Kai-yue Lu; Yan-hui Shi; Peng Zhang (Natural Product Research, 2025)

Response of invasive Solidago canadensis to foliar application of natural herbicide and glyphosate - Muhammad Anas; Zhi-Yun Huang; HuAnHe Xiong; Muhammad Imran; Meng-Ting Yan; Qaiser Javed; Guang-Qian Ren; Shan-Shan Qi; Jian Li; Zhi-Cong Dai; Dao-Lin Du (Journal of Environmental Management, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

The dietary supplementation with probiotic Bacillus cereus G1-11 improved the growth parameters, immune performances, intestinal histomorphology, and disease resistance of hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Ming-Qing Zhang; Zhong-Xuan Zhong; Qian-Ping Du; Wen Li; Ya-Ting Zhu; Guang-Ting Xie; Feng-Ying Yan; Jin-Lin Yang; Shui-Sheng Li; Hu Shu (Animal Feed Science and Technology, 2025)

Unrecognized emissions and health risks of intermediate-volatility organic compounds in vehicle cabins: Insights from a nontargeted analytical approach - Haoning Chang; Yajun Wu; Jing Zhang; Dianjia Liu; Yao Zeng; Pengfei Song; Jinsheng Zhang; Yan Liu; Lin Wu; Ting Wang; Hongjun Mao; Jianfei Peng; et al. (Journal of Hazardous Materials, 2025)

Earthworm-assisted shift and enrichment of the active di(2-ethylhexyl) phthalate degraders in farmland soils by DNA-stable isotope probing - Ting Wei; Zhen Zhen; Shuwen Luo; Yijie Chen; Jin Li; Yan-Qiu Liang; Mengke Song; Jincheng Li; Zhong Lin; Dayi Zhang (Journal of Hazardous Materials, 2025)

Stable two dimensional copper(II) based metal-organic framework as an efficient peroxymonosulfate activator for tetracycline degradation - Jia-Ting Chen; Wan-Yi Wang; Si-Tong Chen; Wen-Bin Chen; Yan-Yong Lin; Meng Yang; Wen Dong (Journal of Environmental Chemical Engineering, 2025)

Effect of low-energy stirring temperature on the formation of oil-in-water emulsions stabilized by gelatin-arginine complexes - Jun Qi; Yu-cong Li; Hui-min Yan; Li-ting Zeng; Ao-jing Lv; Rui-ling Dong; Xue-qing Li; Zhou Lin; Le-le Shao; Lang Zhang; Guo-qing Duan; Chun-hui Zhang; et al. (Food Research International, 2025)

Polycyclic aromatic hydrocarbon aggravates high-fat diet-induced metabolic dysfunction-associated steatotic liver disease through disturbing hepatocyte sphingolipid metabolism - Hui-Ru Kuo; Yu-Fen Chung; Li-Ting Wang; Chih-Wen Wang; Shih-Hsien Hsu; Li-Chen Chen; Ming-Hong Lin; Shau-Ku Huang; Kwei-Yan Liu (Environmental Pollution, 2025)

Green antibiotic breakthrough: Short–rotation woody crops pulp waste liquor defeats drug-resistant bacterial biofilms - Yan Lin; Ting Jiao; Jian Jiao; Ming Zhang; Wentao Wang (Chemical Engineering Journal, 2025)

Senegenin ameliorates diabetic encephalopathy via promoting mitophagy and repressing NLRP3 inflammasome activation - Xiao-dan Yan; Yu Yang; Wan-ting Zhang; Qing-quan Kong; Xi-tong Zheng; Lin-sen Li; Qing Yu (Psychopharmacology, 2025)

Fabrication of nonionic surfactant modified montmorillonite for alginate/organo-montmorillonite composite fibers based hydrophobic pharmaceutical formulations - Yanan Bu; Xiuqiong Chen; Ting Wu; Jiji Fan; Haizhen Dai; Huiqiong Yan; Qiang Lin (Applied Clay Science, 2025)

Coffee mitigated cognitive impairments in sleep-deprived mice by regulating circadian rhythm, inflammation, oxidative stress, and intestinal ecology - Hui-Bin Jiang; Fen-Fen Wei; Wen-Ting Li; Zi-Han Lin; Chuang Zhu; Yan Wu; Ying Wang; Li-Hua Song (Food Bioscience, 2025)

Viscosity is a nonnegligible factor in the waste activated sludge fermentation: Taking hyaluronan as an example - Yan-Lin Hu; Kun Dai; Qing-Ting Wang; Chen-Yuan Zhou; Xing-Chen Huang; Xiao-Fei Yang; He-Liang Pang; Raymond Jianxiong Zeng; Fang Zhang (Water Research, 2025)

Tissue and cell types infected by Ecytonucleospora hepatopenaei (EHP) - Yuan Wang; Shi-ting Lin; Ming Zhao; Peng Di; Jun-fang Zhou; Shou-hu Li; Yan-qing Huang; Ying Na; Xin-cang Li; Wen-hong Fang (Journal of Invertebrate Pathology, 2025)

Tailoring Cu3Nx clusters on TiO2 nanosheets to the sub-nanometric scale for enhancing NH3 photosynthesis - Hyun Sik Moon; Yu-Jeong Yang; Getasew Mulualem Zewdie; Geon Youn; Yi-An Chen; Yu-Peng Chang; Kai-Chi Hsiao; Ting-Han Lin; Yi-Dong Lin; Jun Kue Park; Jucheol Park; Yan-Gu Lin; et al. (Chemical Engineering Journal, 2025)

Mechanistic insights into endometriosis: roles of Streptococcus agalactiae and L-carnitine in lesion development and angiogenesis - Yuan Zhuang; Ting Lyu; Yang Chen; Wei Li; Lei Tang; Shi-ping Xian; Peng-fei Yang; Lijie Wang; Qian-qian Zhang; Chaoming Mei; Yu-jing Lin; Zhixiang Yan; et al. (Angiogenesis, 2025)

Effects of novel bio-organic fertilizer on the remediation of PAEs-contaminated soil and its bacterial community composition - Hong-Jia Huang; Bogui Pan; Qi-Feng Liang; Wan-Ting Zhang; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Chemical Engineering, 2025)

Harnessing microalgae: Pioneering strategies for cost-effective EPA synthesis - Yi-Ting Shen; Zi-Xu Zhang; Xin Qi; Hong-Xuan Wu; Yan-Cheng Lin; Wang Ma; Guang Yang; Xiao-Man Sun (Food Bioscience, 2025)

Molecular mechanisms based on peripheral level of vanillin recognition in Orthaga achatina (Lepidoptera: Pyralidae) - Ting-Ting Yang; Yu Ma; Zheng Dai; Ying Li; Ji-Xiang Wang; Teng-Fei Bai; Merid Negash Getahun; George F.O. Obiero; Shuang-Lin Dong; Jin Zhang; Qi Yan (Insect Biochemistry and Molecular Biology, 2025)

Beneficial impact of MTGase-modified fish gelatin on collagen supplementation in rats: Insights from serum metabolomics and gut microbiota - Chun-Yan Peng; Ting Fang; Hao-Bin Lin; Ni Zhang; Zi-Zi Hu; Hai-tao Wang; Ming-Hui Su; Xiao-Mei Sha; Zong-Cai Tu (Food Research International, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

A feasibility study on cortisol and cortisone as biomarkers for psychological stress in wastewater-based epidemiology - Xue-Ting Shao; Yan-Song Wang; Zhen-Fang Gong; Yan-Ying Li; Jian-Guo Lin; De-Gao Wang (Water Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Correction to: Scorpion Venom Heat-Resistant Peptide is Neuroprotective Against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2025)

Arsenic and its associated metabolism genes in Chinese soils: a comprehensive investigation of mine and paddy soils - Yu-Ting Lin; Rui-Lian Yu; Gong-Ren Hu; Jing-Wei Sun; Yu Yan (Journal of Soils and Sediments, 2025)

Metabolic outcomes of Cordyceps fungus and Goji plant polysaccharides during in vitro human fecal fermentation - Fang Ting Gu; Jun Hui Li; Zi Chen Zhao; Yan Yu Zhu; Lin Xi Huang; Jian Yong Wu (Carbohydrate Polymers, 2025)

The link between eye movements and cognitive function in mild to moderate Alzheimer’s disease - Xiao-ting Ma; Lin-lin Yao; Shan-wen Liu; Xiao-fen Weng; Run-ying Bao; Yi-fan Yang; Yi-feng Li; Yan-yun Sun; Dan Xu; Zhen-yu Jia; Hua Hu (Experimental Brain Research, 2025)

Associations of maternal serum concentration of iron-related indicators with gestational diabetes mellitus in Chinese: A pilot prospective cohort study - Geng-dong Chen; Peng-sheng Li; Zi-xing Zhou; Ting-ting Pang; Hai-yan Wang; Xiao-yan Gou; Shao-xin Ye; Dong-xin Lin; Da-zhi Fan; Zheng-ping Liu (Journal of Trace Elements in Medicine and Biology, 2024)

Bifidogenic properties of polysaccharides isolated from mushroom Lentinula edodes and enhanced immunostimulatory activities through Bifidobacterial fermentation - Lin Xi Huang; Fang Ting Gu; Yan Yu Zhu; Zi Chen Zhao; Jun Hui Li; Jian Yong Wu (Food Bioscience, 2024)

Effects of Limosilactobacillus reuteri on ruminal microbiota, muscle protein metabolism, and flavor of Sunit lamb - Ting Liu; Maoqin Zhai; Taiwu Zhang; Min Zhang; Chenlei Wang; Yanni Zhang; Yan Duan; Lin Su; Ye Jin; Lina Sun (Food Bioscience, 2024)

Linking joint exposures to residential greenness and air pollution with adults’ social health in dense Hong Kong - Ting Zhang; Bo Huang; Sensen Wu; Jie Chen; Yizhen Yan; Yinyi Lin; Hung Wong; Samuel Yeung-Shan Wong; Roger Yat-Nork Chung (Environmental Pollution, 2024)

Nature-inspired temperature-adaptive module: Achieving all-season passive thermal regulation for buildings - Lin Liang; Jianheng Chen; Kaixin Lin; Xueming Yang; Sai Liu; Chui Ting Kwok; Hao Pan; Ziai Liu; Aiqiang Pan; Siru Chen; Yihao Zhu; Wei Li; et al. (Energy and Buildings, 2024)

Increase of PCSK9 expression in diabetes promotes VEGFR2 ubiquitination to inhibit endothelial function and skin wound healing - Jian-Jun Gao; Fang-Yuan Wu; Yu-Jia Liu; Le Li; Yi-Jun Lin; Yue-Ting Kang; Yue-Ming Peng; Yi-Fang Liu; Chen Wang; Zhen-Sheng Ma; Yang Cao; Hong-Yu Cao; et al. (Science China Life Sciences, 2024)

A ZnO-nanorod/PEDOT:PSS nanocomposite functionalized bridge-like membrane type nanomechanical sensing device for ultrasensitive blood lead detection - Yi-Kuang Yen; Chia-Ming Yang; Chen-Ting Kao; Tzung-Hai Yen; Ragurethinam Shanmugam; Yan-Lin Chen; Hwai-En Lin (Analytica Chimica Acta, 2024)

Intrauterine exposure to long-chain perfluorocarboxylic acids (PFCAs) were associated with reduced primary bile acids in three-year-old children: Findings from a prospective birth cohort study - Yu-Ting Guo; Jin-bo Huang; Jing-chuan Xue; Shuang-Jian Qin; Dan Cai; Qi-Zhen Wu; Chu Chu; Cui-lan Tang; Yan-qi Xie; Li-Zi Lin; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2024)

Simulated human digestion and fermentation of a high-molecular weight polysaccharide from Lentinula edodes mushroom and protective effects on intestinal barrier - Jun Hui Li; Fang Ting Gu; Ye Yang; Zi Chen Zhao; Lin Xi Huang; Yan Yu Zhu; Shiguo Chen; Jian Yong Wu (Carbohydrate Polymers, 2024)

Hepatic and metabolic outcomes induced by sub-chronic exposure to polystyrene microplastics in mice - Sheng-Han Lee; Ting-An Lin; Yuan-Horng Yan; Chu-Chun Chien; Tsun-Jen Cheng (Archives of Toxicology, 2024)

Female urinary incontinence in China after 15 years’ efforts: Results from large-scale nationwide surveys - Jiming Zhu; Haiyu Pang; Peicheng Wang; Yanhua Chen; Huihui Li; Qing Liu; Luwen Wang; Hangmei Jin; Liyan Gong; Jingyan Xie; Ting Lai; Aiyang Li; et al. (Science Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A novel nitric oxide-driven nanomotor for synergistic treatment of ischaemic stroke: Enhanced deep brain penetration and therapeutic efficacy - Zhicheng Xiao; Yi Li; Ting Chen; Chenchen Xie; Jun Liao; Pu Lin; Zhe-Sheng Chen; Yan Qiu; Jian Cai; Chuan Zhang; Tingfang Wang (Chemical Engineering Journal, 2024)

A high-entropy strategy for stable structure of sodium ion batteries: From fundamentals to applications - Xu Liu; Xin-Yu Liu; Nan Zhang; Peng-Fei Wang; Zong-Lin Liu; Jun-Hong Zhang; Jie Shu; Yan Sun; Chun-Sheng Li; Ting-Feng Yi (Chemical Engineering Journal, 2024)

Prevention and control strategies for antibiotic resistance: from species to community level - Yan-Zi Wang; Hu Li; Qing-Lin Chen; Ting Pan; Yong-Guan Zhu; Dirk Springael; Jian-Qiang Su (Soil Ecology Letters, 2024)

The mitigation of citric acid on cadmium toxicity in Iris tectorum and its effects on the composition of cell walls - Xiao-Fang Yu; Zhi-Wen Wang; Feng-Lian Chen; Mao-Lin Chen; Xin-Yu Zhang; Jun-Rui Zhang; Wen-Yu Ji; Xue Xiao; Li-Juan Yang; Ting Lei; Xi Li; Ming-Yan Jiang (International Biodeterioration & Biodegradation, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

HO-1 activation contributes to cadmium-induced ferroptosis in renal tubular epithelial cells via increasing the labile iron pool and promoting mitochondrial ROS generation - Yan-Ting Lv; Tian-Bin Liu; Yue Li; Zhen-Yong Wang; Cai-Yu Lian; Lin Wang (Chemico-Biological Interactions, 2024)

Correction to: The connection between six common air pollution particles and adult brain tumors: a meta-analysis of 26,217,930 individuals - Lu-Ting Shen; Meng-Wei Ge; Fei-Hong Hu; Yi-Jie Jia; Wen Tang; Wan-Qing Zhang; Dan-Yan Zhao; Wang-Qin Shen; Hong-Lin Chen (Environmental Science and Pollution Research, 2024)

Inorganic and organic nutrients in tropical–subtropical Western Pacific coral reef waters - Huei-Ting Lin; Vianney Denis; Chih-Chiang Hsieh; Chieh-Jhen Chen; Wanchien Victoria Hsiao; Pei-Ling Wang; Chih-Chieh Su; Yan-Ning Kuo (Coral Reefs, 2024)

Heterogeneity of phosphorus sources invokes distinct niche partitioning pathways of ectomycorrhizal fungi in forest soils - Xianying Lin; Chen Ning; Ting Liu; Dandan Gao; Andrew R. Smith; Wende Yan; Shuguang Liu (Soil Biology and Biochemistry, 2024)

Cellulose-derived raw materials towards advanced functional transparent papers - Yanhua Guan; Li Yan; Hai Liu; Ting Xu; Jinghuan Chen; Jikun Xu; Lin Dai; Chuanling Si (Carbohydrate Polymers, 2024)

Berberine hydrochloride delays citrus sour rot mainly by disrupting carbohydrate and energy metabolism of Geotrichum citri-aurantii spores - Lu Li; Bo Lin; Yu Ting; Maohui Li; Jinjin Hu; Jingjing Song; Yingjuan Yan; Jiaxin Chen; Hong Xiao; Nengguo Tao (Pesticide Biochemistry and Physiology, 2024)

Liquefaction and post-liquefaction behaviors of unreinforced and geogrid reinforced calcareous sand - Lin Zhou; Jian-Feng Chen; Yan Zhu; Ting Yao (Geotextiles and Geomembranes, 2024)

3D Visualization of Whole Brain Vessels and Quantification of Vascular Pathology in a Chronic Hypoperfusion Model Causing White Matter Damage - Yang Wu; Jia Ke; Song Ye; Li-Li Shan; Shuai Xu; Shu-Fen Guo; Meng-Ting Li; Tian-Ci Qiao; Zheng-Yu Peng; Yi-Lin Wang; Ming-Yuan Liu; He Wang; et al. (Translational Stroke Research, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Fully automated learning and predict price of aquatic products in Taiwan wholesale markets using multiple machine learning and deep learning methods - Yi-Ting Lai; Yan-Tsung Peng; Wei-Cheng Lien; Yun-Chiao Cheng; Yi-Ting Lin; Chen-Jie Liao; Yu-Shao Chiu (Aquaculture, 2024)

Discrete recoil control system modelling and optimal recoil damping of deepwater drilling riser systems - Bao-Lin Zhang; Yue-Ting Sun; Yan-Dong Zhao; Qing-Long Han; Xian-Ming Zhang; Zhihui Cai (Ocean Engineering, 2024)

Differentiation of closely-related species within Acinetobacter baumannii-calcoaceticus complex via Raman spectroscopy: a comparative machine learning analysis - Xue-Song Xiong; Lin-Fei Yao; Yan-Fei Luo; Quan Yuan; Yu-Ting Si; Jie Chen; Xin-Ru Wen; Jia-Wei Tang; Su-Ling Liu; Liang Wang (World Journal of Microbiology and Biotechnology, 2024)

Sulfate-functionalized Fe-based MOF for removal of Pb(Ⅱ) and NO3- in industrial wastewater - Rui-Dong Wang; Wen-Qian Zhang; Hong-Bo Lv; Yan-Ting Chen; Lei Wang; Si-Han Zhou; Lin Du; Qi-Hua Zhao (Journal of Environmental Chemical Engineering, 2024)

Regulating framework aluminum location towards boosted light olefins generation in ex-situ catalytic pyrolysis of low-density polyethylene - Ting Wang; Xiang Feng; Dong Lin; Yan Li; Jingyuan Shang; Jinqing Zhang; Shuo Li; Yibin Liu; Hui Zhao; Zhe Ma; Xiaobo Chen; Xingong Zhang; et al. (Chemical Engineering Journal, 2024)

Tailpipe volatile organic compounds (VOCs) emissions from Chinese gasoline vehicles under different vehicle standards, fuel types, and driving conditions - Peiji Liu; Yajun Wu; Zongxuan Li; Zongyan Lv; Jinsheng Zhang; Yan Liu; Ainan Song; Ting Wang; Lin Wu; Hongjun Mao; Jianfei Peng (Atmospheric Environment, 2024)

Intelligent response organo-montmorillonite/Fe3+-alginate/poly (N-isopropylacrylamide) interpenetrating network composite hydrogels for controlled release of water-insoluble pesticides - Hongcai Wang; Xiuqiong Chen; Cuiyu Gong; Yanan Bu; Ting Wu; Huiqiong Yan; Qiang Lin (Applied Clay Science, 2024)

Effects of urbanization and topography on thermal comfort during a heat wave event: A case study of Fuzhou, China - Zefeng Zheng; Xinlu Lin; Li Chen; Chao Yan; Ting Sun (Sustainable Cities and Society, 2024)

Investigating the impact of high-altitude on vehicle carbon emissions: A comprehensive on-road driving study - Zhiwen Jiang; Lin Wu; Haomiao Niu; Zhenyu Jia; Zhaoyu Qi; Yan Liu; Qijun Zhang; Ting Wang; Jianfei Peng; Hongjun Mao (Science of The Total Environment, 2024)

Glyphosate drives autophagy-dependent ferroptosis to inhibit testosterone synthesis in mouse Leydig cells - Lu Lu; Cai-Yu Lian; Yan-Ting Lv; Shu-Hui Zhang; Long Wang; Lin Wang (Science of The Total Environment, 2024)

The immune response of Caspase-3 gene in infectious hypodermal and hematopoietic necrosis virus (IHHNV) infection of Litopenaeus vannamei - Cai-Yi Chen; Ning Yang; Chuanyu He; Yang Gao; Lin-Rui Chang; Ting Li; Ling-Jun Si; Dong-Chun Yan (Aquaculture, 2024)

Taste traces: Capsaicin and sweeteners as anthropogenic markers in municipal wastewater - Xue-Ting Shao; Yan-Song Wang; Yue-Tong Zhao; Jian-Guo Lin; Wei Pei; Ming-Xing Guo; De-Gao Wang (Science of The Total Environment, 2024)

Triclocarban exhibits higher adipogenic activity than triclosan through peroxisome proliferator-activated receptors pathways - Jia-Da Zhang; Sen He; Ting-Ting He; Chuan-Hai Li; Bing-Hua Yan; Yuan Yang; Jian Yang; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Environmental Pollution, 2024)

A ratiometric fluorescent probe based on the FRET platform for the detection of sulfur dioxide derivatives and viscosity - Feng-Ting Liu; Peng-Fei Jiang; Yan-Pu Wang; Bao-Xiang Zhao; Zhao-Min Lin (Analytica Chimica Acta, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Surveillance of COVID-19 and influenza A(H1N1) prevalence in China via medicine-based wastewater biomarkers - Xue-Ting Shao; Yan-Song Wang; Zhen-Fang Gong; Yan-Ying Li; Dong-Qin Tan; Jian-Guo Lin; Wei Pei; De-Gao Wang (Water Research, 2023)

Enhanced expression of RAGE/NADPH oxidase signaling pathway and increased level of oxidative stress in brains of rats with chronic fluorosis and the protective effects of blockers - Yan-Lin Ma; Jie Deng; Ting Zhang; Hong-Mei Li; Qiu-Zhe Liang; Kai-Lin Zhang (Journal of Trace Elements in Medicine and Biology, 2023)

STAT6 promoting oxalate crystal deposition-induced renal fibrosis by mediating macrophage-to-myofibroblast transition via inhibiting fatty acid oxidation - Tianhui Yuan; Yuqi Xia; Shengyu Pan; Bojun Li; Zehua Ye; Xinzhou Yan; Weimin Hu; Lei Li; Baofeng Song; Weimin Yu; Haoyong Li; Ting Rao; et al. (Inflammation Research, 2023)

Effects of different Solanum sect. Solanum (Solanaceae) straw amendments on selenium accumulation and growth of grapevine - Kewen Huang; Xu Chen; Ran Zhang; Yiping Dong; Qunxian Deng; Yan Huang; Lei Liu; Ting Wang; Ming’an Liao; Lijin Lin (Acta Physiologiae Plantarum, 2023)

Development of a duplex PCR for the simultaneous detection of EHP and IHHNV and analysis of the correlation between these two pathogens - Yang Gao; Cai-Yi Chen; Zheng Cao; Ru-Qing Yuan; Lin-Rui Chang; Ting Li; Ling-Jun Si; Dong-Chun Yan; Fan Li (Journal of Invertebrate Pathology, 2023)

Three new compounds from Anoectochilus roxburghii (Wall.) Lindl - Yan-Lin Bin; Shun-Zhi Liu; Ting-Ting Xie; Wen-Zheng Feng; Hao-Yang Li; Zi-Jia Ye; Zhi-Hao Dong; Ying-Kun Qiu (Natural Product Research, 2023)

The connection between six common air pollution particles and adult brain tumors: a meta-analysis of 26,217,930 individuals - Lu-Ting Shen; Meng-Wei Ge; Fei-Hong Hu; Yi-Jie Jia; Wen Tang; Wan-Qing Zhang; Dan-Yan Zhao; Wang-Qin Shen; Hong-Lin Chen (Environmental Science and Pollution Research, 2023)

Environmental exposure and ecological risk of perfluorinated substances (PFASs) in the Shaying River Basin, China - Ya-Hui Zhang; Ting-Ting Ding; Zi-Yan Huang; Hong-Yi Liang; Shi-Lin Du; Jin Zhang; Hui-Xian Li (Chemosphere, 2023)

Anodic oxidation-accelerated self-reconstruction of tri-metallic Prussian blue analogue toward robust oxygen evolution reaction performance - Thi Xuyen Nguyen; Kai-Hsiang Yang; Yan-Jia Huang; Yen-Hsun Su; Oliver Clemens; Rui-Kun Xie; Yu-Jung Lin; Jyh-Fu Lee; Jyh-Ming Ting (Chemical Engineering Journal, 2023)

The effect of platinum-group minerals on differentiation of platinum-group elements in magmatic sulfide deposits: Evidence from the Cu-Ni-PGE deposits in the Yangliuping area of the Emeishan large igneous province, SW China - Qing-Lin Liang; Xie-Yan Song; Ting-Mao Long; Richard Wirth; Zhi-Hui Dai (Chemical Geology, 2023)

Size-dependent chemical composition of atmospheric nanoparticles in urban Beijing during springtime - Yan Chen; Chenjuan Deng; Ting Lei; Junling Li; Chaofan Lian; Yiran Li; Jun Zheng; Jun Zhao; Dongbin Wang; Zhijun Wu; Lin Wang; Lei Li; et al. (Atmospheric Environment, 2023)

Genesis of No. 2 orebody of the Jinchuan magmatic Ni-Cu-(PGE) sulfide deposit, NW China: New constraints from the newly discovered deep extension - Ting-Mao Long; Xie-Yan Song; Jian Kang; Qing-Lin Liang; Yong-Cai Wang; De-Xian Li; Qi-Xing Ai; Wen-De Suo; Jian-Quan Lu (Mineralium Deposita, 2023)

Evaluating vehicular exhaust and evaporative emissions via VOC measurement in an underground parking garage - Yajun Wu; Yan Liu; Peiji Liu; Luna Sun; Pengfei Song; Jianfei Peng; Ruikang Li; Ning Wei; Lin Wu; Ting Wang; Lina Zhang; Ning Yang; et al. (Environmental Pollution, 2023)

Investigating the stretchability of doped poly(3-hexylthiophene)-block-poly(butyl acrylate) conjugated block copolymer thermoelectric thin films - Qing-Bao Zheng; Yan-Cheng Lin; Yen-Ting Lin; Yun Chang; Wei-Ni Wu; Jhih-Min Lin; Shih-Huang Tung; Wen-Chang Chen; Cheng-Liang Liu (Chemical Engineering Journal, 2023)

Toward ultra-high efficiency tandem OLEDs: Benzothiazole-based bipolar hosts and specific device architectures - Jui-Ming Wang; Ting-Chun Lee; Chia-Chen Chung; Wun-Yu Chen; Sih-Yu Wu; Yan-Ding Lin; Yuan Jay Chang; Chin-Wei Lu; Chih-Hao Chang (Chemical Engineering Journal, 2023)

Population structure and genetic diversity of Triticum araraticum Jakubz. and Triticum timopheevii Zhuk. - Ting Peng; Xiaomei Jiang; Dinghao Wang; Minghu Zhang; Xin Liu; Ming Hao; Wei Li; Dengcai Liu; Bo Jiang; Lin Huang; Shunzong Ning; Zhongwei Yuan; et al. (Genetic Resources and Crop Evolution, 2023)

Study on the Mechanism of Arsenic-Induced Lung Injury Based on SWATH Proteomics Technology - Yi Wang; Jun Zhang; Xinglai Zhang; Huajie Zhang; Xueshan Cao; Ting Hu; Jing Lin; Xiaoxiao Tang; Xiaolu Chen; Yuxuan Jiang; Xi Yan; Hongbin Zhuang; et al. (Biological Trace Element Research, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Study of infectious hypodermal and hematopoietic necrosis virus (IHHNV) infection in different organs of Penaeus vannamei - Zi-Hao Hou; Yang Gao; Jing-Jing Wang; Cai-Yi Chen; Lin-Rui Chang; Ting Li; Ling-Jun Si; Fan Li; Dong-Chun Yan (Journal of Invertebrate Pathology, 2023)

Development of a high-fidelity failure prediction system for reinforced concrete bridge columns using generative adversarial networks - Ting-Yan Wu; Rih-Teng Wu; Ping-Hsiung Wang; Tzu-Kang Lin; Kuo-Chun Chang (Engineering Structures, 2023)

High entropy promoted active site in layered double hydroxide for ultra-stable oxygen evolution reaction electrocatalyst - Thi Xuyen Nguyen; Chia-Chien Tsai; Van Thanh Nguyen; Yan-Jia Huang; Yen-Hsun Su; Siang-Yun Li; Rui-Kun Xie; Yu-Jung Lin; Jyh-Fu Lee; Jyh-Ming Ting (Chemical Engineering Journal, 2023)

CircFhit Modulates GABAergic Synaptic Transmission via Regulating the Parental Gene Fhit Expression in the Spinal Dorsal Horn in a Rat Model of Neuropathic Pain - Ting Xu; Zhen-Yu Li; Meng Liu; Su-Bo Zhang; Huan-Huan Ding; Jia-Yan Wu; Su-Yan Lin; Jun Liu; Jia-You Wei; Xue-Qin Zhang; Wen-Jun Xin (Neuroscience Bulletin, 2023)

Experimental Study on Fractal Characteristics of Surface Roughness of Briquettes and their Effect on Wettability of Coal Samples - Min Yan; Hanxi Luo; Ting Yang; Dongjie Yan; Jianing Wei; Haifei Lin; Shugang Li (Natural Resources Research, 2023)

Identification and Pathogen Stimulation Patterns of Neuronal Nitric Oxide Synthase (nNOS) in Black Rockfish (Sebastes schlegelii) - Xu Yan; Ningning Wang; Min Cao; Chao Li; Ning Yang; Ting Xue; Qiang Fu; Lin Song (Journal of Ocean University of China, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Street-view and traditional greenness metrics with adults' sitting time in high-density living in Hong Kong: Comparing associations, air pollution and noise roles, and population heterogeneity - Ting Zhang; Bo Huang; Yizhen Yan; Yinyi Lin; Hung Wong; Samuel Yeung-shan Wong; Roger Yat-Nork Chung (Science of The Total Environment, 2023)

Associations of residential greenness with unhealthy consumption behaviors: Evidence from high-density Hong Kong using street-view and conventional exposure metrics - Ting Zhang; Bo Huang; Yizhen Yan; Yinyi Lin; Hung Wong; Samuel Yeung-shan Wong; Roger Yat-Nork Chung (International Journal of Hygiene and Environmental Health, 2023)

Effect of ferulic acid covalent conjugation on the functional properties and antigenicity of β-lactoglobulin - Yu-Ting Xue; Ya-Ning Han; Yan Wang; Ying-Hua Zhang; Yu-Qi Yin; Bo-Hao Liu; Han-Lin Zhang; Xin-Huai Zhao (Food Chemistry, 2023)

Coral reef resilience persisted for a millennium but has declined rapidly in recent decades - Ting Zhang; Tianran Chen; Sheng Liu; Xianzhi Lin; Shu Li; Wen Yan (Frontiers in Marine Science, 2023)
The lack of long-term records of coral community composition restricts our understanding of the contemporary ecological states of tropical reefs. Here we integrated paleo-ecological reconstruction, historical mortality evidence, and ecological survey data to determine the temporal variability in reef resilience of the Nansha atolls in the tropical western Pacific. Subfossil coral assemblages extracted from the reef cores exhibited no evidence of community shifts attributable to centennial-scale changes in El Niño variability during the last millennium, suggesting long-term stability in community structure and persistence of reef resilience. By contrast, ecological surveys revealed a major collapse in the reef ecosystem, and high-precision U-series dating of dead Acropora fragments indicated that this collapse occurred in recent decades and was especially relevant to several strong/extreme El Niño episodes. Frequent and intensive El Niño−Southern Oscillation and marine heatwaves have overwhelmed the reefs’ resistive and recovery capacity, thereby impairing reef resilience.

Triclocarban and triclosan exacerbate high-fat diet-induced hepatic lipid accumulation at environmental related levels: The potential roles of estrogen-related receptors pathways - Xin Li; Jia-Da Zhang; Han Xiao; Sen He; Ting-Ting He; Xiao-Min Ren; Bing-Hua Yan; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2023)

Performance and mechanisms of biochar-assisted vermicomposting in accelerating di-(2-ethylhexyl) phthalate biodegradation in farmland soil - Zhen Zhen; Shuwen Luo; Yijie Chen; Gaoyang Li; Huijun Li; Ting Wei; Fengcheng Huang; Lei Ren; Yan-Qiu Liang; Zhong Lin; Dayi Zhang (Journal of Hazardous Materials, 2023)

Structure, Intracellular Localisation and Expression Analysis of Sucrose Nonfermenting-Related Kinase ShSnRK1α in Sugarcane - Ting-ting Zhao; Jun-gang Wang; Wen-zhi Wang; Cui-lian Feng; Xiao-yan Feng; Lin-bo Shen; Shu-zhen Zhang (Sugar Tech, 2023)

Dynamic Co-Simulation Analysis and Control of an IEA 15 MW Offshore Floating Semi-Submersible Wind Turbine under Taiwan Offshore-Wind-Farm Conditions of Wind and Wave - Cherng-Jer Chueh; Chun-Hung Chien; Ching Lin; Ting-Yan Lin; Mao-Hsiung Chiang (Journal of Marine Science and Engineering, 2023)
This study aims to develop dynamic co-simulation and control for analyzing the IEA 15 MW semi-submersible floating wind turbine under Taiwan offshore-wind-farm conditions of wind and wave. The IEA 15 MW wind turbine is mounted on a UMaine VolturnUS-S reference platform with a mooring system designed for a water depth of 70 m, in this study. The dynamic co-simulation combines software of SIMPACK, MATLAB/SIMULINK, AeroDyn, HydroDyn, WAMIT, and MAP++ to achieve the complex dynamic simulation of aerodynamics, hydrodynamics, mechanism dynamics and control system dynamics. In addition, this study proposes a novel power-control strategy combining fuzzy sliding-mode control with additional pitching-rate feedback. Since the motion of the floating platform, especially the pitching motion, contributes to power oscillation, the proposed novel power-control strategy with additional pitching-rate feedback can reduce the influence of the floating-platform oscillation motion, and is verified under different conditions.

Observer-based dynamic optimal recoil controller design for deepwater drilling riser systems - Wei Zhang; Bao-Lin Zhang; Qing-Long Han; Yue-Ting Sun; Yan Ji; Dawei Zhang; Xian-Ming Zhang (Ocean Engineering, 2023)

Extract of Ginkgo biloba leaves attenuates neurotoxic damages in rats and SH-SY5Y cells exposed to a high level of fluoride - Jie Xiang; Yan-Lin Ma; Jian Zou; Xiao-Xiao Zeng; Xiao Xiao; Yan-Long Yu; Yang-Ting Dong; Long-Yan Ran; Xiao-Lan Qi; Wei Hong; Yan-Hui Gao; Zhi-Zhong Guan (Journal of Trace Elements in Medicine and Biology, 2023)

Measurement of atmospheric nanoparticles: Bridging the gap between gas-phase molecules and larger particles - Chao Peng; Chenjuan Deng; Ting Lei; Jun Zheng; Jun Zhao; Dongbin Wang; Zhijun Wu; Lin Wang; Yan Chen; Mingyuan Liu; Jingkun Jiang; Anpei Ye; et al. (Journal of Environmental Sciences, 2023)

A pectic polysaccharide from fresh okra (Abelmoschus esculentus L.) beneficially ameliorates CCl4-induced acute liver injury in mice by antioxidation, inhibition of inflammation and modulation of gut microbiota - Jing-Kun Yan; Chun Wang; Ting-Ting Chen; Jie Zhu; Xu Chen; Longqing Li; Xiaozhen Liu; Henan Zhang; Lin Li (Food and Chemical Toxicology, 2023)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Effect of gravel content on the detachment of colluvial deposits in Benggang - Li-ting Zhang; Fang Shuai; Li-bo Chen; Yan-he Huang; Jin-shi Lin; Yue Zhang; Hong-li Ge; Fang-shi Jiang (Journal of Mountain Science, 2022)

Testing the transfer functions for the Geonor T-200B and Chinese standard precipitation gauge in the central Qinghai—Tibet Plateau - Le-le Zhang; Li-ming Gao; Ji Chen; Lin Zhao; Ke-long Chen; Jing-yi Zhao; Guo-jun Liu; Ting-xi Song; Yan-kun Li (Journal of Mountain Science, 2022)

First report of Euphorbia leaf curl virus infecting Passiflora edulis in Fujian province, China - Ting Ye; Guo-Hua Zheng; Ying Guo; Yan-Lin Ming (Journal of Plant Pathology, 2022)

Highly selective monoclonal antibody-based lateral flow immunoassay for visual and sensitive determination of conazole fungicides propiconazole in vegetables - Ze-Ke Xu; Jing-Nan Meng; Yi Lei; Xing-Xing Yang; Yi-Yong Yan; Hai-Hong Liu; Hong-Tao Lei; Ting-Cai Wang; Xing Shen; Zhen-Lin Xu (Food Additives & Contaminants: Part A, 2022)

Species Composition and Assemblages of Ichthyoplankton in Sansha Bay, Fujian Province, China - Yan Jiang; Bai-an Lin; Hao-yang He; Guang-mao Ding; Li-ting Yan; Ge Zhang; Min Liu; Lian-ming Zheng (Frontiers in Marine Science, 2021)
Sansha Bay (26.40−27.00°N, 119.50−120.20°E) is a typical semi-enclosed bay, located in northern Fujian Province, China, and adjacent to the East China Sea. The ichthyoplankton species composition and assemblage structure were investigated based on monthly sampling at 25 stations in April−September 2019, covering the important spring and summer spawning seasons in the region. Sampling was conducted in the first 3−5 days of the full moon or new moon phases using a standard plankton net through horizontal and vertical tows during daytime. In total, 25,819 ichthyoplankton samples were collected, of which 25,449 samples (i.e., 24,757 eggs and 692 larvae) were from horizontal tows. For horizontal tow samples, the ichthyoplankton were classified into 58 taxa in 15 orders and 23 families with a combination of external morphology and DNA barcoding analyses, from pelagic to demersal and benthic species. The dominant order was the Gobiiformes, including 23 species (39.7% of all species). The dominant taxa, in terms of relative abundance and frequency of occurrence, consisted of commercially important fishes, such as Setipinna tenuifilis (Valenciennes, 1848) (Engraulidae), Epinephelus akaara (Temminck and Schlegel, 1842) (Serraenidae), Collichthys lucidus (Richardson, 1844), Nibea albiflora (Richardson, 1846) (Sciaenidae), Acanthopagrus schlegelii (Bleeker, 1854), and Pagrus major (Temminck and Schlegel, 1843) (Sparidae), accounting for 78.9% of the horizontal tow samples. Low-valued and small-sized fishes, such as Stolephorus commersonnii Lacepède, 1803 (Engraulidae), Solea ovata Richardson, 1846 (Soleidae), Nuchequula nuchalis (Temminck and Schlegel, 1845), and Photopectoralis bindus (Valenciennes, 1835) (Leiognathidae), were also dominant species, accounting for 11.4% of the horizontal tow samples. The ichthyoplankton assemblage was categorized into five different temporal assemblages based on the cluster and nonmetric multidimensional scaling analysis, namely, April, May, June, July, and August−September (ANOSIM, Global R = 0.656, p < 0.01) with the highest density and richness of ichthyoplankton occurred in May. The spatial distribution pattern showed that the high density (ind./m 3 ) of ichthyoplankton occurred mainly in S12–S25 in Guanjingyang and along the Dongchong Peninsula coastline into Dongwuyang, while low density occurred mainly in S01–S11 in the northwest waters of Sandu Island (ANOVA, F = 8.270, p < 0.05). Temperature, salinity, and chlorophyll a were key factors structuring the ichthyoplankton assemblages in Sansha Bay. In addition, this study revealed the changes of the ichthyoplankton composition, density, and spatial distribution in Sansha Bay over the past three decades.

Timing and magnitude of climatic extremes differentially elevate mortality but enhance recovery in a fish population - Ming‐Chih Chiu; Shih‐Hsun Chang; Yu‐Ting Yen; Lin‐Yan Liao; Hsing‐Juh Lin (Global Change Biology, 2021)
The countervailing effects of disturbances (e.g., high mortality and enhanced recovery) on population dynamics can occur through demographic processes under rapidly increasing climatic extremes. Across an extreme‐event gradient, we mechanistically demonstrated how dramatic changes in streamflow have affected the population persistence of endangered salmon in monsoonal Taiwan over a three‐decade period. Our modeling indicated that the dynamics of the age‐structured population were attributed to demographic processes, in which extensive mortality was characterized as a function of climatic extremes and vulnerability in the young stage of fish. In the stochastic simulations, we found that the extensive mortality and high proportion of large fish resulted from extreme flooding, which caused high values of postimpact population recovery. Our empirical evidence suggests that the magnitudes and timing of disturbance can explain the population persistence when facing climatic extremes and thereby challenges the understanding of the mechanistic drivers of these countervailing phenomena under changing environmental conditions.

Degraded polysaccharides from Porphyra haitanensis: purification, physico-chemical properties, antioxidant and immunomodulatory activities - Yun-Feng Huo; Yin-Ting Li; Wei Xia; Chong Wang; Yuan-Yuan Xie; Yan-Bo Wang; Tao Zhou; Ling-Lin Fu (Glycoconjugate Journal, 2021)

Applying Artificial Intelligence (AI) Techniques to Implement a Practical Smart Cage Aquaculture Management System - Chung-Cheng Chang; Jung-Hua Wang; Jenq-Lang Wu; Yi-Zeng Hsieh; Tzong-Dar Wu; Shyi-Chy Cheng; Chin-Chun Chang; Jih-Gau Juang; Chyng-Hwa Liou; Te-Hua Hsu; Yii-Shing Huang; Cheng-Ting Huang; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose This paper presents our team’s results to establish an AIoT smart cage culture management system. Methods According to the built system, the farmed field information is transmitted to the data platform of Ocean Cloud, and all collected data and analysis results can be applied to the cage culture field after the bigdata analysis. Results This management system successfully integrates AI and IoT technologies and is applied in cage culture. Using underwater biological analysis images and AI feeding as examples, this paper explains how the system integrates AI and IoT into a feasible framework that can constantly acquire information about the health status of fish, survival rate of fish, as well as the feed residuals. Conclusion The results of our research enable the aquaculture operators or owners to efficiently reduce the feed residual, monitor the growth of fish, and increase fish survival rate, thereby increasing the feed conversion rate.

The relationship between anthocyanin accumulation and photoprotection in young leaves of two dominant tree species in subtropical forests in different seasons - Zheng-Chao Yu; Wei Lin; Xiao-Ting Zheng; Wah Soon Chow; Yan-Na Luo; Min-Ling Cai; Chang-Lian Peng (Photosynthesis Research, 2021)

The hand-arm vibration syndrome associated with the grinding of handheld workpieces in a subtropical environment - Nuoyan Wei; Hansheng Lin; Ting Chen; Bin Xiao; Maosheng Yan; Li Lang; Hongyu Yang; Shan Wu; Paul-Émile Boileau; Qingsong Chen (International Archives of Occupational and Environmental Health, 2021)

Population-based meta-analysis of chloroquine: informing chloroquine pharmacokinetics in COVID-19 patients - Xueting Yao; Xiaoyu Yan; Xiaohan Wang; Ting Cai; Shun Zhang; Cheng Cui; Xiaoxu Wang; Zhe Hou; Qi Liu; Haiyan Li; Jing Lin; Zi Xiong; et al. (European Journal of Clinical Pharmacology, 2021)
Aims Chloroquine (CQ) has been repurposed to treat coronavirus disease 2019 (COVID-19). Understanding the pharmacokinetics (PK) in COVID-19 patients is essential to study its exposure–efficacy/safety relationship and provide a basis for a possible dosing regimen optimization. Subject and methods In this study, we used a population-based meta-analysis approach to develop a population PK model to characterize the CQ PK in COVID-19 patients. An open-label, single-center study (ethical review approval number: PJ-NBEY-KY-2020-063-01) was conducted to assess the safety, efficacy, and pharmacokinetics of CQ in patients with COVID-19. The sparse PK data from 50 COVID-19 patients, receiving 500 mg CQ phosphate twice daily for 7 days, were combined with additional CQ PK data from 18 publications. Results A two-compartment model with first-order oral absorption and first-order elimination and an absorption lag best described the data. Absorption rate (ka) was estimated to be 0.559 h −1 , and a lag time of absorption (ALAG) was estimated to be 0.149 h. Apparent clearance (CL/F) and apparent central volume of distribution (V2/F) was 33.3 l/h and 3630 l. Apparent distribution clearance (Q/F) and volume of distribution of peripheral compartment (Q3/F) were 58.7 l/h and 5120 l. The simulated CQ concentration under five dosing regimens of CQ phosphate were within the safety margin (400 ng/ml). Conclusion Model-based simulation using PK parameters from the COVID-19 patients shows that the concentrations under the currently recommended dosing regimen are below the safety margin for side-effects, which suggests that these dosing regimens are generally safe. The derived population PK model should allow for the assessment of pharmacokinetics–pharmacodynamics (PK-PD) relationships for CQ when given alone or in combination with other agents to treat COVID-19.

Assisted selection of eating quality progeny of indica (O. sativa L. ssp. indica) and japonica (O. sativa L. ssp. japonica) hybrids using rice starch properties - Ting Mao; Zhan Zhang; Shan Jun Ni; Yi Zhou Zhao; Xin Li; Li Li Zhang; Yan Liu; Cheng Shun Zhong; He Huang; Shao Lin Wang; Xu Li (Genetic Resources and Crop Evolution, 2021)

One new sterpurane sesquiterpene from cultures of the basidiomycete Pholiota nameko - Wan-Rong Niu; Cong-Liang Guo; Deng-Ji Lou; Rui-Ting Li; Qiao Xiang; Yu-Lin Zou; Xiu-Ming Cui; Xiao-Yan Yang (Natural Product Research, 2020)

Multiplex RT–PCR Assay for the Simultaneous Detection and Identification of Five Sugarcane Viruses - Xiao-Yan Feng; Wen-Zhi Wang; Lin-Bo Shen; Jun-Gang Wang; Guo-Ru Xiong; Cui-Lian Feng; Ting-Ting Zhao; Shu-Zhen Zhang (Sugar Tech, 2020)

Synergistic effects of pazopanib and hyperthermia against uterine leiomyosarcoma growth mediated by downregulation of histone acetyltransferase 1 - Chiao-Yun Lin; Angel Chao; Ren-Chin Wu; Li-Yu Lee; Shir-Hwa Ueng; Chia-Lung Tsai; Yun-Shien Lee; Meng-Ting Peng; Lan-Yan Yang; Huei-Jean Huang; Hsin-Shih Wang; Chyong-Huey Lai (Journal of Molecular Medicine, 2020)

Scorpion Venom Heat-Resistant Peptide is Neuroprotective against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2020)

Allelopathy confers an invasive Wedelia higher resistance to generalist herbivore and pathogen enemies over its native congener - Shan-Shan Qi; Yan-Jie Liu; Zhi-Cong Dai; Ling-Yun Wan; Dao-Lin Du; Rui-Ting Ju; Justin S. H. Wan; Stephen P. Bonser (Oecologia, 2020)

Characteristics, Expression Pattern and Intracellular Localisation of Sugarcane Cytoplasmic Hexokinase Gene ShHXK8 - Jun-gang Wang; Ting-ting Zhao; Ben-peng Yang; Wen-zhi Wang; Cui-lian Feng; Xiao-yan Feng; Lin-bo Shen; Shu-zhen Zhang (Sugar Tech, 2019)

Deriving water quality criteria for China for the organophosphorus pesticides dichlorvos and malathion - Ting-ting Ding; Ya-hui Zhang; Yan Zhu; Shi-lin Du; Jin Zhang; Ying Cao; Yi-zhe Wang; Gong-ting Wang; Lian-sheng He (Environmental Science and Pollution Research, 2019)

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

Cold water immersion test (10 °C, 10 min) for diagnosing vibration-induced white finger among a group of polishers in a subtropical environment - Bin Xiao; Danying Zhang; Maosheng Yan; Hongying Qu; Wei Wen; Xiao Zhang; Hansheng Lin; Ying Ye; Ting Chen; Qingsong Chen (International Archives of Occupational and Environmental Health, 2019)

The Characteristics of Climate Change and Adaptability Assessment of Migratory Bird Habitats in Wolonghu Wetlands - Jun Ma; Baisha Weng; Wuxia Bi; Dengming Yan; Meng Li; Ting Xu; Lina Wang; Lin Wang (Wetlands, 2019)

First report of lettuce big-vein associated varicosavirus infecting lettuce in China - Guo-Hua Zheng; Ting Ye; Fu-Rong Liao; Wen-Zhu Zhang; Yan-Lin Ming (Journal of Plant Pathology, 2019)

Development of a Reverse Transcription-Recombinase Polymerase Amplification Assay for Detection of Sugarcane Yellow Leaf Virus - Xiao-Yan Feng; Lin-Bo Shen; Wen-Zhi Wang; Jun-Gang Wang; Zheng-Ying Cao; Cui-Lian Feng; Ting-Ting Zhao; Shu-Zhen Zhang (Sugar Tech, 2018)

Immune Cells After Ischemic Stroke Onset: Roles, Migration, and Target Intervention - Lu-yao Ao; Yun-Yi Yan; Lin Zhou; Cheng-yuan Li; Wan-Ting Li; Wei-rong Fang; Yun-man Li (Journal of Molecular Neuroscience, 2018)

Neuroinflammation and Neuroimmunomodulation in Alzheimer’s Disease - Yin Hong; Jun Xu; Yue Hu; Lin Li; Zhen Dong; Ting-ke Zhu; Yan-qiu Wei (Current Pharmacology Reports, 2018)

Comparative pharmacokinetics study of five alkaloids in rat plasma and related compound–herb interactions mechanism after oral administration of Shuanghua Baihe tablets - Xinyu Zhao; Yan Wang; Lu Zheng; Chengpeng Sun; Chao Wang; Haijian Cong; Ting Xiang; Lin Zhang; Houli Zhang; Sa deng; Baojing Zhang; Bin Wu; et al. (Natural Product Research, 2018)

Phylogenetic analysis of IRIS L. from China on chloroplast TRNL-F sequences - Yu-Lin Jiang; Zhuo Huang; Jin-Qiu Liao; Hui-Xing Song; Xiao-Mei Luo; Su-Ping Gao; Ting Lei; Ming-Yan Jiang; Yin Jia; Qi-Bing Chen; Xiao-Fang Yu; Yong-Hong Zhou (Biologia, 2018)

Significance of temperature and water availability for soil phosphorus transformation and microbial community composition as affected by fertilizer sources - Dasheng Sun; Qingfang Bi; Kejie Li; Peibin Dai; Yan Yu; Weiwei Zhou; Ting Lv; Xipeng Liu; Jun Zhu; Qichun Zhang; Chongwei Jin; Lingli Lu; et al. (Biology and Fertility of Soils, 2018)

Molecular phylogeography and paleodistribution modeling of the boreal tree species Ulmus lamellosa (T.Wang et S. L. Chang) (Ulmaceae) in China - Li Liu; Wei Chen; Dong-Ting Yan; Jing Li; Lin Liu; Yi-Ling Wang (Tree Genetics & Genomes, 2017)

Sonic Hedgehog Signaling Affected by Promoter Hypermethylation Induces Aberrant Gli2 Expression in Spina Bifida - Xiao-Lin Lu; Li Wang; Shao-Yan Chang; Shao-Fang Shangguan; Zhen Wang; Li-Hua Wu; Ji-Zhen Zou; Ping Xiao; Rui Li; Yi-Hua Bao; Z-Y Qiu; Ting Zhang (Molecular Neurobiology, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Cracking Process and Stress Field Evolution in Specimen Containing Combined Flaw Under Uniaxial Compression - Ting Liu; Baiquan Lin; Wei Yang; Quanle Zou; Jia Kong; Fazhi Yan (Rock Mechanics and Rock Engineering, 2016)

Characterization and utilization of microsatellites in the Coffea canephora genome to assess genetic association between wild species in Kenya and cultivated coffee - Collins Ogutu; Ting Fang; Lin Yan; Lu Wang; Lifang Huang; Xiaoyang Wang; Baiquan Ma; Xianbao Deng; Albert Owiti; Aggrey Nyende; Yuepeng Han (Tree Genetics & Genomes, 2016)

Context- and time-dependent neurobiological and behavioral sensitization induced by a single morphine exposure in mice - Wang-Jun Qin; Yan-Ting Wang; Peng-Mei Li; Xiao-Xing Wang; Jun-Xu Li; Hamid R. Noori; Rick E. Bernardi; Jian-Hui Liang; Xiang-Lin Zhang (Psychopharmacology, 2016)

Involvement of NADPH oxidases and non-muscle myosin light chain in senescence of endothelial progenitor cells in hyperlipidemia - Ting-Bo Li; Jie-Jie Zhang; Bin Liu; Wei-Qi Liu; Yan Wu; Xiao-Ming Xiong; Xiu-Ju Luo; Qi-Lin Ma; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

G206D Mutation of Presenilin-1 Reduces Pen2 Interaction, Increases Aβ42/Aβ40 Ratio and Elevates ER Ca2+ Accumulation - Wei-Ting Chen; Yi-Fang Hsieh; Yan-Jing Huang; Che-Ching Lin; Yen-Tung Lin; Yu-Chao Liu; Cheng-Chang Lien; Irene Han-Juo Cheng (Molecular Neurobiology, 2015)

Voriconazole: a novel treatment option for cryptococcal meningitis - Yan Yao; Jia-Tang Zhang; Bo Yan; Ting Gao; Xiao-Wei Xing; Cheng-Lin Tian; Xu-Sheng Huang; Sheng-Yuan Yu (Infectious Diseases, 2015)

Crack propagation patterns and energy evolution rules of coal within slotting disturbed zone under various lateral pressure coefficients - Lin Bai-quan; Liu Ting; Zou Quan-le; Zhu Chuan-jie; Yan Fa-zhi; Zhang Zhen (Arabian Journal of Geosciences, 2015)

Microcalorimetry studies of the antimicrobial actions of Aconitum alkaloids - Yan-bin Shi; Lian Liu; Wei Shao; Ting Wei; Gui-mei Lin (Journal of Zhejiang University-SCIENCE B, 2015)

Protective Effect of Apigenin on Ischemia/Reperfusion Injury of the Isolated Rat Heart - Jing Hu; Zilin Li; Li-ting Xu; Ai-jun Sun; Xiao-yan Fu; Li Zhang; Lin-lin Jing; An-dong Lu; Yi-fei Dong; Zheng-ping Jia (Cardiovascular Toxicology, 2015)

Novel Link of Anti-apoptotic ATF3 with Pro-apoptotic CTMP in the Ischemic Brain - Chien-Yu Huang; Jin-Jer Chen; Jui-Sheng Wu; Hsin-Da Tsai; Heng Lin; Yu-Ting Yan; Chung Y. Hsu; Yuan-Soon Ho; Teng-Nan Lin (Molecular Neurobiology, 2015)

IL-12 could induce monocytic tumor cells directional differentiation - Ting-ting Ma; Bi-Tao Wu; Yan Lin; Hai-Yu Xiong; Qin Wang; Zi-Wei Li; Feng Cheng; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2015)

Activation of Extracellular Signal-Regulated Kinase1/2 in the Medial Prefrontal Cortex Contributes to Stress-Induced Hyperalgesia - Jian Qi; Chen Chen; Ya-Cheng Lu; Ting Zhang; Hao Xu; Yuan-Yuan Cui; Yan-Zhou Chen; Wen Wang; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2014)

Identification of the substrate recognition region in the Δ6-fatty acid and Δ8-sphingolipid desaturase by fusion mutagenesis - Li-Ying Song; Yan Zhang; Shu-Fen Li; Jun Hu; Wei-Bo Yin; Yu-Hong Chen; Shan-Ting Hao; Bai-Lin Wang; Richard R.-C. Wang; Zan-Min Hu (Planta, 2014)

The relationship between typhoons' peripheral circulation and ground-level ozone concentrations in central Taiwan - Wan-Li Cheng; Li-Wei Lai; Walter Den; Meng-Ting Wu; Chao-An Hsueh; Pay-Liam Lin; Chueh-Ling Pai; Yeou-Lih Yan (Environmental Monitoring and Assessment, 2014)

Isolation and characterization of novel ginsenoside-hydrolyzing glycosidase from Microbacterium esteraromaticum that transforms ginsenoside Rb2 to rare ginsenoside 20(S)-Rg3 - Lin-Hu Quan; Chao Wang; Yan Jin; Ting-Rui Wang; Yeon-Ju Kim; Deok Chun Yang (Antonie van Leeuwenhoek, 2013)

Association of the apolipoprotein M gene polymorphisms and serum lipid levels - Lynn Htet Htet Aung; Rui-Xing Yin; Dong-Feng Wu; Ting-Ting Yan; Qing Li; Jin-Zhen Wu; Wei-Xiong Lin; Cheng-Wu Liu; Shang-Ling Pan (Molecular Biology Reports, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

Expression of MMP-9 in hepatic sinusoidal obstruction syndrome induced by Gynura segetum - Xia-zhen Yu; Tao Ji; Xue-li Bai; Liang Liang; Lin-yan Wang; Wei Chen; Ting-bo Liang (Journal of Zhejiang University-SCIENCE B, 2013)

An Improved AhR Reporter Gene Assay for Analyzing Dioxins in Soil, Sediment and Fish - How-Ran Chao; Ya-Fan Wang; Yao-Nan Wang; Ding-Yan Lin; Yan-You Gou; Chien-Yu Chen; Kuan-Chung Chen; Wen-Kai Wu; Bao-An Chiang; Yu-Ting Huang; Lien-Te Hsieh; Kuei-Jyum C. Yeh; et al. (Bulletin of Environmental Contamination and Toxicology, 2012)

SIRT1 is required for long-term growth of human mesenchymal stem cells - Hong-Feng Yuan; Chao Zhai; Xin-Long Yan; Dan-Dan Zhao; Jing-Xue Wang; Quan Zeng; Lin Chen; Xue Nan; Li-Juan He; Si-Ting Li; Wen Yue; Xue-Tao Pei (Journal of Molecular Medicine, 2012)

Impact of simulated microgravity on microvascular endothelial cell apoptosis - Chun-Yan Kang; Lin Zou; Ming Yuan; Yang Wang; Tian-Zhi Li; Ye Zhang; Jun-Feng Wang; Yan Li; Xiao-Wei Deng; Chang-Ting Liu (European Journal of Applied Physiology, 2011)

Fast Cleanup System Combined with a Dioxin-responsive Element-driven Luciferase Bioassay for Analysis of Polychlorinated Dibenzo-p-dioxins/furans in Sediments and Soils - How-Ran Chao; Ya-Fen Wang; Ding-Yan Lin; Yi-Ting Cheng; Tsui-Chun Tsou (Bulletin of Environmental Contamination and Toxicology, 2011)

Preparation of high-affinity rabbit monoclonal antibodies for ciprofloxacin and development of an indirect competitive ELISA for residues in milk - Bin Huang; Yun Yin; Lei Lu; Hai Ding; Lin Wang; Ting Yu; Jia-jin Zhu; Xiao-dong Zheng; Yan-zhen Zhang (Journal of Zhejiang University-SCIENCE B, 2010)

Isolation and characterization of polymorphic microsatellite loci in Aquilaria sinensis (Lour.) Gilg - Yan-Ting Zhang; Zheng-Feng Wang; Hong-Lin Cao; Xiao-Yi Li; Lin-Fang Wu; Shu-Bin Zhuo; Xiao-Feng Huang (Conservation Genetics Resources, 2010)

Degradation of phenanthrene by the endophytic fungus Ceratobasidum stevensii found in Bischofia polycarpa - Chuan-chao Dai; Lin-shuang Tian; Yu-ting Zhao; Yan Chen; Hui Xie (Biodegradation, 2010)

The distribution of HBV genotypes and clinical significance in familial clustering in an infected population with unfavorable prognosis - Jinfeng Liu; Yongqin Li; Tianyan Chen; Yuan Yang; Ke Wang; Yingli He; Qian Yang; Feng Ye; Yan Jin; Ting Qiu; Shumei Lin; Min Liu; et al. (Archives of Virology, 2008)

Tetrandrine suppresses LPS-induced astrocyte activation via modulating IKKs-IκBα-NF-κB signaling pathway - Shu-Ting Lin; Ying Wang; Yang Xue; De-Chun Feng; Yan Xu; Ling-Yun Xu (Molecular and Cellular Biochemistry, 2008)

System for automatic generalization of topographic maps - Hao-wen Yan; Zhi-lin Li; Ting-hua Ai (Chinese Geographical Science, 2006)